Practical Hive : a guide to Hadoop's data warehouse system /: a guide to Hadoop's data warehouse system. (2016) - Shaw, Scott, 1970-; Vermeulen, Andreas François; Gupta, Ankur, 1978-; Kjerrumgaard, David
No abstract available